Space Exploration of AlN Pedestal Waveguides for Phase Shifting Applications - Jara F. (2021)
F. J., R.R., and M.A. acknowledge funding support from CONCYTEC-FONDECYT within the call E041-01 [contract number 015-2018-FONDECYT/BM].